ETHNOBOTANICAL POTENTIAL OF Carica papaya, Psidium guajava AND Azadirachta indica LEAF, BARK EXTRACTS AND THEIR COMBINATION IN INHIBITING THE GROWTH OF Salmonella typhi - Odeje, Salifu Christopher; Rabia, Hanga (FUDMA Journal of Sciences, 2026)
The rise of antibiotic resistance among bacterial pathogens, including Salmonella typhi, represents a significant public health challenge worldwide. Salmonella typhi, the causative agent of typhoid fever, continues to cause high morbidity and mortality among people especially in developing countries. An Isolates of Salmonella typhi was obtained from Aminu Kano Teaching Hospital, Kano and treated with three different concentrations (50, 75 and 100 mg/ml) of Azadirachta indica, Psidium Guajava and Carica papaya using disc diffusion method. The results revealed that all the treatments were highly significantly effective against the test organism. The leaf extracts were more effective against the growth of Salmonella typhi than the bark and the combined. Similarly, Carica papaya performed better against the test organism than both A. indica and P. guajava. However, Azadirachta performed better (17.71 mm) than the other treatments (8.86 mm for P. guajava and 11.89 mm for C. papaya.) when combined. The effects of the concentration revealed that the concentration of 100 mg/ml was most effective across all the test materials. Based on the results obtained from this study, it can be concluded that the test materials highly inhibit the growth of Salmonella typhi. Similarly, the leaves of the test materials are more effective than the barks. Also, the leaf of Carica papaya inhibited more Salmonella than either P. guajava or Azadirachta indica.